Designing of a Shell and Tube Heat Exchanger for Methyl Chloride Production - Nurhaliza, Amanda; Bayu Dani Nandiyanto, Asep (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
This study focuses on the design and performance analysis of a shell-and-tube heat exchanger engineered explicitly for effectively handling methyl chloride in industrial applications. While the application of heat exchangers in various industrial processes is well-documented, methyl chloride’s distinct chemical and physical properties necessitate a specialized design approach. This research begins with a thorough review of existing literature and prior designs to identify the key considerations and challenges in developing an optimized heat exchanger for methyl chloride. The design process adheres to the standards set forth by the Tubular Exchanger Manufacturers Association (TEMA), ensuring compliance with established dimensional specifications. Critical parameters related to the working fluid are meticulously defined and evaluated. Performance analysis is conducted through manual calculations, facilitated by Microsoft Excel, to assess the heat exchanger’s operational efficiency. The results indicate that the designed heat exchanger meets and exceeds the required standards, featuring 85 tubes and an effectiveness value exceeding 75%. The high effectiveness value underscores the heat exchanger’s robust operational performance. It is a reliable component for industrial processes involving methyl chloride.